I want to prove double negation introduction in sequent calculus using the most basic rule set.

That is what I want to prove: from the sequent $$\Gamma \rightarrow\Phi,$$ the sequent $$\Gamma \rightarrow\neg\neg\Phi$$ is derivable.

How is this accomplished? It's seems much more difficult than in natural deduction. I think I may be able to prove the conjunction myself once I have this result.

  • $\begingroup$ Do you have the negation sign as primitive or it is defined in terms of $\supset$ and $\bot$ ? $\endgroup$ – Mauro ALLEGRANZA Feb 13 '17 at 8:18

With $\lnot$ as primitive, we have to use $\text {L-} \lnot$ followed by : $\text {R-} \lnot$:

\begin{align} {\cfrac{{\cfrac{\Gamma \to \Delta, A }{\lnot A, \Gamma \to \Delta} \text {L-} \lnot}}{\Gamma \to \Delta, \lnot \lnot A }\text {R-} \lnot} \end{align}

With $\lnot A$ defined as $A \supset \bot$, we have to use $\text {L-} \supset$ followed by : $\text {R-} \supset$:

\begin{align} {\cfrac{\cfrac{{\cfrac{\Gamma \to \Delta, A \quad \quad \bot, \Gamma \to \Delta }{A \supset \bot, \Gamma \to \Delta} \text {L-} \supset}}{A \supset \bot, \Gamma \to \Delta, \bot}\text {R-W}}{\Gamma \to \Delta, (A \supset \bot) \supset \bot }\text {R-} \supset} \end{align}

Note : the top-right sequent is:

\begin{align} {\cfrac{ }{\bot, \Gamma \to \Delta} \text {L-} \bot} \end{align}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.